The relationships between service quality and customer satisfaction of a courier service provider: towards more focus approach / Hartini Zuhaila Jamal, Faliza Mahamed Ali and Roseazrina Azmi - Jamal, Hartini Zuhaila; Mahamed Ali, Faliza; Azmi, Roseazrina (Universiti Teknologi MARA, Cawangan Melaka, 2018)
The purpose of this paper is to identify the relationship between reliability, responsiveness, empathy, assurance and tangible towards customer satisfaction in one of the courier service provider in Shah Alam, Selangor. The methodology is based on customer satisfaction models with SERVQUAL survey input to investigate the relationships of the five dimensions towards the customer satisfaction. The survey data were collected via a convenience sample of the customers who visited the courier service provider at the targeted location in early 2018. To achieve the objectives, a multiple regression analysis is conducted to test the relationships of each dimension towards customer satisfaction. The study found that out of the five SERQUAL dimensions, only reliability, responsiveness and assurance does have a relationship with customer satisfaction at the courier service provider. The limitations of the current study include the small sample size in which it should be conducted with a bigger population and several outlets of the targeted courier service provider. Further research may focus more on determinants factor in customer loyalty, improving service quality and performing cross-institutional benchmarking. For theoretical implication, it has added new knowledge to the literature of factors that affect customer satisfaction and led to new findings in which was found to be different from previous researches. For practical implication, it helps to give more awareness to the courier service manager to be aware of the problems in order for them to increase the service efficiencies.